ANALISIS PUTUSAN TENTANG PENAMBANGAN PASIR ILEGAL DI TULUNGAGUNG (STUDI PUTUSAN NOMOR : 62/Pis.Sus/PN.Ta) - setyawan, didik (Universitas Negeri Surabaya, 2021)
Keywords : Mining is an activity carried out by digging into the ground (earth) to get something in the form of mining products. The optimal use of natural resources can improve the welfare of human living standards is the hope of the whole community. In the application of the regulations in conducting mining include business licenses in this case are Mining Business Permits, People's Mining Business Permits, and Special Mining Business Permits. However, many miners who conduct mining are not accompanied by procedures and permits that apply in Indonesia, which can be said mining is carried out illegally. The purpose of this study is to determine whether the judge has given a sense of justice to the community and the government. The research method used is normative juridical, the approach used consists of a statutory approach, a case approach, and a conceptual approach. This study Analyzes the Judge's Decision NUMBER: 62 / Pis.Sus / PN.Ta in trying the defendant. The results of this study are expected to provide views or considerations for judges in considering decisions to obtain a sense of justice and provide a deterrent effect for perpetrators in committing criminal mining activities illegal. Mining, Mining Business Permie, Ilegal Mining, Research Purposes, Court Decision, Research Result